Evaluation of sports services to be provided by local governments by rural area managers (village headmen). Example of elazig province - Bingolbali, Abdullah; Mendes, Bekir (Lahore Medical & Dental Coll, 2021)
Background: The villages, which are the smallest of the local government and rural units, have increased their proximity to the cities with the developing technological opportunities and thanks to the developing mass media, the desire to present the social, sportive, and cultural opportunities offered in the cities to the villages has increased. Aim: This study was planned to determine the views of village headmen in rural areas on the sports services to be provided by local governments to the countryside. Methods: In the research, semi-structured and in-depth interviews were conducted with 30 Headmen using the phenomenology design which is one of the qualitative research methods. The collected data were analyzed by content analysis and descriptive analysis methods. In this context, the expressions obtained from the opinions of headmen were themed. Results: when the opinions of the Headmen who participated in the study were examined, it was observed that the explanations they expressed were compatible with scientific studies. When the issue is looked at from this point of view, it has been determined that the evaluations of the headmen on local governments and sports issues are at a level that cannot be underestimated. Conclusion: In our research, it has been revealed that local administrations do not give sufficient support to the villages regarding sports activities. Most of the headmen stated that they will not be taken care of and their demands will not be taken into consideration. In this study, the sensitivity of the village headmen, who are considered as the closest service unit to the public, regarding sports services and youth, and their thoughts on serving them are important in terms of showing the level of Turkish society.
Keywords: Local Governments; Village Headmen; Sports Services; Elazig; Rural Area